Use of multiple antidiabetic medications in patients with diabetes and its association with hypoglycaemic events: a case-crossover study in Jordan. Issue 11 (21st November 2018) - Naser, Abdallah Y; Wong, Ian Chi Kei; Whittlesea, Cate; Beykloo, Maedeh Y; Man, Kenneth K C; Lau, Wallis C Y; Hyassat, Dana Abdel-Halim; Wei, Li
Abstract : Objective: To assess whether the use of multiple antidiabetic medications is associated with an increased risk of hypoglycaemia in patients with type 2 diabetes mellitus. Design: A case-crossover study. Setting: Cases were enrolled from the National Center for Diabetes, Endocrinology and Genetics in Amman, Jordan. Participants: Patients were those with diabetes mellitus and reported incident of a hypoglycaemic event in their medical records during the period January 2007 to July 2017. Patients with multiple antidiabetic medications were those with at least two antidiabetic medications. Primary outcome: History of antidiabetic medication use was extracted from the pharmacy records. The use of multiple antidiabetic medications during the risk window (before hypoglycaemia) was compared with a control window(s) (earlier time) of the same length after a washout period. Conditional logistic regression was applied to evaluate the OR of hypoglycaemia between the treatment groups. A secondary analysis was performed in patients with a blood glucose measurement of ≤70 mg/dL. Results: 182 patients (106 females, 58.2%) were included in the study with an average age of 59.9 years (SD=9.9). The patients' average body mass index was 31.7 kg/m 2 (SD=6.2). Compared with monotherapy, the OR of hypoglycaemic events for patients with multiple antidiabetic medications was 5.00 (95% CI 1.10 to 22.82). The OR was 6.00 (95% CI 0.72 to 49.84) for the secondary analysis patient group (n=94). Ten-fold increased risk was found in patients (n=155) with insulin and sulfonylurea-based combination therapy (OR 10.00;95% CI 1.28 to 78.12). Conclusion: This study shows that the use of multiple antidiabetic medications appears to increase the risk of hypoglycaemic events. Patients and healthcare professionals should be extra vigilant when patients are on multiple antidiabetic medications therapy, especially the combination of sulfonylurea and insulin.